Antifertility effect of turmeric (curcuma longa linn.) rhizome ethanolic extracts on female mice - Alimagno, Zarina Joselle S.; Marohomsalic, Haniah Nuska; Santos, Ann Charmaine Cabigas
Curcuma longa Linn (Fam. Zingiberacea) is a rhizomatous herbaceous perennial plant widely distributed in the Philippines. It has diverse traditional uses in which the curcuminoids present in the rhizomes can cat as antifertility agent. This exploratory study aimed to evaluate the antifertility activity of Curcuma linga Linn. Rhizome ethanolic extracts on female mice C. longa rhizomes were subjected to extraction using ethanol as solvent. The extract obtained was then qualitatively characterized through phytochemical screening and thin layer chromatography. The extract was further divided for the three treatment groups with doses 250, 500 and 1000 mg/kg BW/day and was compared to the negative (10% Tween 20) and positive (Ethinyl estradiol-Levonorgestrel) control groups. The doses were administered for 10 days after which the female mice were allowed to mate and undergo gestation period. Relative organ weights and pregnancy ratios were determined to assess the success in preventing pregnancy of the extracts. Basis for pregnancy ratio included macroscopic and histologic examination of the reproductive organs of female mice. Qualitative analyses revealed the possible presence of curcuminoids detected through the presence of characteristic yellow spots in all visualization techniques done ? daylight inspection, UV light (254 and 365 nm) and through its antioxidant property using DPPH spray. Assessment for success in preventing mice pregnancy also revelaed the antifertility effect of the extracts through the following findings: (1) 1000 mg/kg dose has a significantly lower relative organ weight than the negative control group and (2) all three doses used ? 250, 500 and 1000 mg/kg have 0% pregnancy ratio as compared with 67% and 0% pregnancy ration of the negative and positive control groups, respectively. Signs of toxicity were also observed on the 500 and 1000 mg/kg doses used. The crude rhizome ethanolic extract of C. longa exhibited antifertility effects in all three treatment doses used. However, beginning at 500 mg/kg dose, signs of toxicity were already observed. Further studies are needed to establish toxicity profile and minimum effective dose of Curcuma longa Linn.
Thesis (Bachelor of Science in Pharmacy)--University of the Philippines Manila, 2015.
Keywords: Curcuma longa linn; Antifertility